Postconcussion Depressive Symptoms and Clinical Assessment Associations in Adolescents. Issue 2 (2021) - Callahan, Christine E.; Moore, Robert Davis; Kay, Jacob J.M.; Colwell, Alison; Register-Mihalik, Johna K.; Vesia, Michael; Broglio, Steven P.
ABSTRACT: Purpose: Concussive injury and depression are connected through common overlapping symptoms. This retrospective data analysis aimed to establish an association between postconcussion depressive symptoms and postconcussion clinical measures (concussion symptoms, balance performance, vestibular function, and executive function) while controlling for concussion history, time from injury, age, and sex in concussed adolescents. Methods: Depressive symptoms were assessed using the Beck Depression Inventory for Youth. Postconcussion assessments included the Rivermead Post-Concussion Symptoms Questionnaire, Balance Error Scoring System, Vestibular/Ocular-Motor Screening, and the Behavior Rating Inventory of Executive Function. Separate multiple linear regression models were utilized for each dependent variable (concussion symptoms, balance performance, vestibular function, and executive function). For each model, the primary explanatory variable was depressive symptoms, and covariates included concussion history, time from injury, age, and sex. Results: Depressive symptoms were significantly associated with concussion symptoms ( P < 0.001), vestibular function ( P < 0.05), and executive function ( P = 0.001). Conclusions: This study builds upon current literature surrounding the relationship between concussion and depression by identifying an association between depressive symptoms and postconcussion clinical assessments. These findings highlight the importance of evaluating postconcussive psychological symptoms and may serve to inform future rehabilitation strategies following up concussed adolescents.